Isolasi dan Karakterisasi Enzim Karbohidrase Cairan Rumen Sapi Asal Rumah Potong Hewan - A Budiansyah; B Resmi; K G Wiryawan; D M. T. Soehartono; Y Widyastuti; N Ramli (Faculty of Animal Science, Bogor Agricultural University, 2010)
The aims of this experiment were to identify carbohydrases in rumen liquor of cattle, and to determine optimum temperature and pH of enzymes, as well as to evaluate the effect of metal ions and chemical substances on enzymes activity. Optimum precipitation of the enzymes from local and imported cattle was reached at the concentration of 60% and 70% of ammonium sulphate, respectively. The enzymes (xylanase, mannanase, and amylase) had optimum temperature in the range of 50-60 °C, except for cellulase from imported cattle which had optimum temperature at 39 oC, optimum pH of the enzymes were 6-7 except for cellulase was at pH 4. The enzymes mostly needed methal ions as activators. EDTA and β-mercaptoethanol inhibited activity of cellulase from rumen liquor of local cattle, while enzymes from rumen liquor of imported cattle EDTA inhibited xylanase activity and β-mercaptoethanol inhibited mannanase and amylase activity. Activity of cellulase in rumen liquor of local cattle was higher than those of imported cattle. It is concluded that rumen liquor of imported and local cattles from abbatoir contained cellulase, xylanase, mannase and amylase that most of them had optimum temperature and pH at 50-60 oC and 6-7, respectively, and they needed methal ions as activators. Key words: cattle, rumen liquor, abattoir, enzymes, characterization